The Impact of Domestic Investment and Trade on Economic Growth in North Africa Countries: New Evidence from Panel CS-ARDL Model - Ben Yedder, Nadia; El Weriemmi, Malek; Bakari, Sayef (EuroEconomica, 2023)
The aim of this work is to examine the impact of domestic investment and trade on economic growth in the case of North Africa countries during the period 1990 – 2021 by using Panel CS-ARDL Model. Empirical results indicate that domestic investment and exports don’t have any impact on economic growth in the long run. However, we found that the impact of imports is positive in the long run. These results show that exports and national investments are not considered as a source of economic growth in the country of North Africa over this extended period and suffer from a miserable economic organization and many problems in terms of political and economic instabilities.